The Impact of E-Service Quality and Brand Trust on Repurchase Intention with Customer Satisfaction as Intervening for Telemedicine Application Users - Annisa Dayani; Agung Kresnamurti Rivai; Shandy Aditya (LPPM Universitas Negeri Jakarta, 2022)
As an intervention for Halodoc application users, this study aims to determine the impact of telemedicine application product e-service quality and brand trust on customer satisfaction repurchase intent. We surveyed 245 users of Halodoc applications who performed transactions using Halodoc applications at least once in the past year. The data analysis method used SPSS version 23 and the SEM analysis used LISREL 8.8 to process and analyze the survey data. Hypothesis test results show that quality of e-service has a positive and significant impact on repurchase intention, brand trust has a positive and significant impact on repurchase intention, and quality of e-service has a positive impact on customer satisfaction. It shows that it has a significant impact. Trust has a significant positive impact on customer satisfaction, and customer satisfaction has a significant positive impact on repurchase intention. In addition, the results of this study show a positive and significant indirect relationship between quality of e-service and brand confidence in repurchase intent mediated by customer satisfaction and repurchase intent mediated by customer satisfaction.